Distribution of antimicrobial‐resistant lactic acid bacteria in natural cheese in Japan. (13th October 2013) - Ishihara, Kanako; Nakajima, Kumiko; Kishimoto, Satoko; Atarashi, Fumiaki; Muramatsu, Yasukazu; Hotta, Akitoyo; Ishii, Satomi; Takeda, Yasuyuki; Kikuchi, Masanori; Tamura, Yutaka
ABSTRACT To determine and compare the extent of contamination caused by antimicrobial‐resistant lactic acid bacteria (LAB) in imported and domestic natural cheeses on the Japanese market, LAB were isolated using deMan, Rogosa and Sharpe (MRS) agar and MRS agar supplemented with six antimicrobials. From 38 imported and 24 Japanese cheeses, 409 LAB isolates were obtained and their antimicrobial resistance was tested. The percentage of LAB resistant to dihydrostreptomycin, erythromycin, and/or oxytetracycline isolated from imported cheeses (42.1%) was significantly higher than that of LAB resistant to dihydrostreptomycin or oxytetracycline from cheeses produced in Japan (16.7%; P = 0.04). Antimicrobial resistance genes were detected in Enterococcus faecalis (tetL, tetM, and ermB; tetL and ermB; tetM) E. faecium (tetM), Lactococcus lactis (tetS), Lactobacillus (Lb.), casei/paracasei (tetM or tetW), and Lb. rhamnosus (ermB) isolated from seven imported cheeses. Moreover, these E. faecalis isolates were able to transfer antimicrobial resistance gene(s). Although antimicrobial resistance genes were not detected in any LAB isolates from Japanese cheeses, Lb. casei/paracasei and Lb. coryniformis isolates from a Japanese farm‐made cheese were resistant to oxytetracycline (minimal inhibitory concentration [MIC], 32 µg/mL). Leuconostoc isolates from three Japanese farm‐made cheeses were also resistant to dihydrostreptomycin (MIC, 32 to > 512 µg/mL). In conclusion, the present study demonstrated contamination with antimicrobial‐resistant LAB in imported and Japanese farm‐made cheeses on the Japanese market, but not in Japanese commercial cheeses.